Dionizo Poškos bendrinės kalbos kategorijos - Subačius, Giedrius (Baltistica, 1996)
THE CATEGORIES OF STANDARD LITHUANIAN OF DIONIZAS POŠKA It was Dionizas Poška (ca. 1765 – April 30,1830) who declared that standard Lithuanian should be based on the dialect of the Southern Samogitians near Viduklė (the dūnininkai dialect). The standard language created on this basis, however, was intended to be used in Lithuania Major, not in Lithuania Minor. Lithuania Minor already had its own established tradition of written Lithuanian. By this time Poška was also concerned with the spoken and not only the written standard language. He had plans to publish a dictionary, a grammar of Lithuanian, and a history of Lithuania and he believed that afterwards the standard spoken language might be formed on the basis of these codifying texts. Nevertheless, he imagined future standard spoken Lithuanian not as a pure „dūnininkai” dialect but as sort of synthetic language with some not very clearly envisioned elements of other dialects. During the process of codifying, Poška gave priority to the system of language (to rules and grammaticality) but not to usage. However, even then he also stressed the importance of usage as a supplementary source for the system of language. So it is possible to state that Poška imagined that the future standard language would be created by the southern Samogitians and would be used by all Lithuanians in Major Lithuania, being codified according to the rules (the system) of language and would be spoken the way it would be written. However, it was not fated for his project to be realized.